ANALYSIS OF ISLAMIC LAW ON WORK AGREEMENTS WITH THE PARTNER SYSTEM BETWEEN COMPANIES AND EMPLOYEES: Study on Ninja Xpress Banda Aceh - Imaduddin Abilfada Kusairy (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Couriers are one of the important assets for logistics companies such as Ninja Xpress. In carrying out its business, Ninja Xpress opens vacancies for all Indonesian people to join Ninja Xpress couriers with a partner system. in practice, there is a discrepancy in the payment of wages and bonuses by the company to couriers, so couriers must personally record the number of packages and bonuses that have been delivered to consumers during the month, this is done to avoid the company's actions that arbitrarily avoid its obligations as an employer. The research method used is a qualitative research method with an analytical descriptive approach, data collection techniques are carried out by interviews and documentation as well as literature studies and regulations related to this research. The results of the research show that the form of the Rider Service Agreement between Rider SPH as a service provider and Ninja Xpress as a service recipient is made in writing, and has fulfilled the provisions of the valid terms of the agreement as referred to in Article 1320 Kuhperdata. The Islamic law review of the Ninja Xpress work agreement found that in practice the SPH Rider Service Agreement No. 17792/PKS/HR- SPH Ninja/I/2024 has fulfilled the pillars and conditions of ijarah al-amal, but the concept of ijarah al-amal risk is not in accordance with the provisions due to the transfer of responsibility for damage to goods or loss to Rider SPH as a service provider.